Time-course adaptive changes in hippocampal transcriptome and synaptic function induced by simulated microgravity associated with cognition - Liang, Rong; Wang, Ling; Yang, Qing; Xu, Qing; Sun, Shufan; Zhou, Haichen; Zhao, Meiling; Gao, Jing; Zheng, Chenguang; Yang, Jiajia; Ming, Dong (Frontiers in Cellular Neuroscience, 2023)
The investigation of cognitive function in microgravity, both short-term and long-term, remains largely descriptive. And the underlying mechanisms of the changes over time remain unclear. Initially, we measured the performance of spatial cognition exposed to long-term simulated microgravity (SM). Both working memory and advanced cognitive abilities were enhanced. Somewhat surprisingly, the synaptic plasticity of the hippocampal CA3-CA1 synapse was impaired. To gain insight into the mechanism of changing regularity over time, transcriptome sequencing in the hippocampus was performed. The analysis identified 20 differentially expressed genes (DEGs) in the hippocampus after short-term modeling, 19 of which were up-regulated. Gene ontology (GO) analysis showed that these up-regulated genes were mainly enriched in synapticrelated processes, such as Stxbp5l and Epha6. This might be related to the enhancement of working memory performance under short-term SM exposure. Under exposure to long-term SM, 7 DEGs were identified in the hippocampus, all of which were upregulated and related to oxidative stress and metabolism, such as Depp1 and Lrg1.Compensatory effects occurred with increased modeling time. To sum up, our current research indicates that the cognitive function under SM exposure is consistently maintained or potentially even being enhanced over both short and long durations. The underlying mechanisms are intricate and potentially linked to the differential expression of hippocampal-associated genes and alterations in synaptic function, with these effects being time-dependent. The present study will lay the experimental and theoretical foundation of the multi-level mechanism of cognitive function under space flight.